PLCMIKRO SEBAGAI SOLUSI OTOMATISASI INDUSTRI - Januarto, Eko; Supratno, Setyo (RESULTAN : Jurnal Kajian Teknologi, 2011)
PLC has several advantages including the industry can control the equipment along with the complexity of the sensor device is quite high, thus easing the work of man. PLCMIKRO is designed to use the language ladder (stairs) and use a PIC16F877A microcontroller type as the central processing unit, for the detection sensor is used as an isolation voltage optocoupler with devices outside the microcontroller and the output is used to load its driver transistor relay circuit. PLCMIKRO can communicate with a computer using RS-232 serial communication. PLCMIKRO work after receiving a command in a file after a compiled using software Hexadesimal LDMIKRO and compile the results sent to the microcontroller using software WinPicPgm via RS-232 communication channel.